A rare case of maxillary third molar with four roots and five root canals and its endodontic management with the help of cone-beam computed tomography - Ruchi Shah; Palak P Shah; Nimisha Chinmay Shah; Krupa Himanshu Kapadia; Meetkumar S Dedania (Wolters Kluwer Medknow Publications, 2024)
Maxillary third molars (M3) have unpredictable pulp morphology. They usually have one to three roots; any additional is called an accessory root. Various in vitro and in vivo studies examined its root canal morphology but none of the case reports has been published regarding the successful endodontic treatment of M3 with four roots and five canals. Herein, a case of a 42-year-old male with a complaint of severe pain in M3 is presented. Endodontic treatment was carried out and four canals were negotiated and cleaned. To decipher, the pulp canal complex anatomy cone-beam computed tomography was advised and the presence of the fifth canal (MB2) was confirmed, negotiated, cleaned, and obturated. This report is by far the first case of endodontic treatment of M3 to be reported in the Indian population with four roots and five canals.